Debating NGO accountability - Bendell, Jem (UN New YorkUS, 2006)
Seeks to help those organizations within the UN system and those NGOs that engage with it to develop an understanding of the current debate, and practice, and to reveal some of the myths, as well as pointing towards a more progressive agenda on NGO accountability.